GALLIC ACID PRODUCTION FROM WASTE LOCAL FRUIT IN LOMBOK ISLAND ENZYMATICALLY - Eka Junaidi; Yunita Arian Sani Anwar (UNIVERSITAS SEBELAS MARET (UNS), 2017)
Tannase is industrially important enzyme used in the production of gallic acid. Gallic acid possesses wide range of biological activities such as`antioxidant, antibacterial, and antivirus. This work aims to produce gallic acid from local fruit rind in Lombok enzimatically. The tested rind local fruit were juwet (Syzygium cumini), kepundung (Baccaurea racemosa Muell.Arg) and mangosteen (Garcinia mangostana). The result showed that tannase activity of 57.827 U/mg. Gallic acid concentration has increased with increase in amount of tannase and reaction time. Optimal gallic acid concentration was obtained at 1 % (v/v) tannase and 60 minutes of reaction time for kepundung rind. However, juwet and mangosteen rind produced optimal gallic acid at 1.2 % (v/v) tannase with the same of reaction time.